2010
DOI: 10.1111/j.1365-2230.2009.03700.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the keratin 9 gene in Pakistani families with epidermolytic palmoplantar keratoderma

Abstract: Background-Keratins are heteropolymeric proteins that form the intermediate filament cytoskeleton in epithelial cells. The common basic structure of all keratins is organized in a central α-helical rod domain flanked by nonhelical, variable head and tail regions. Most mutations in keratins are found in the central α-helical rod domain. Keratin 9 (K9) is expressed only in the suprabasal layers of palmoplantar epidermis. Mutations in the keratin 9 gene (KRT9) have been shown to cause epidermolytic palmoplantar k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Mutation screening was carried out in all members of both families as previously reported (Zhang et al, 2005; Shimomura et al, 2010). Using standard protocols, genomic DNA was extracted from the peripheral blood of all members of these two families and 100 unrelated healthy controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation screening was carried out in all members of both families as previously reported (Zhang et al, 2005; Shimomura et al, 2010). Using standard protocols, genomic DNA was extracted from the peripheral blood of all members of these two families and 100 unrelated healthy controls.…”
Section: Methodsmentioning
confidence: 99%
“…EPPK has been attributed to mutations of type I keratin gene clusters which are located at chromosome 17q21 (Reis et al, 1994). Mutations responsible for EPPK have been mainly demonstrated in the Keratin 9 gene ( KRT9 ), which is expressed exclusively in the suprabasal keratinocytes of the palmoplantar epidermis, although there are a few reports on KRT1 mutations dispersed throughout the gene (Reis et al, 1994; Rothnagel et al, 1995; Terron‐Kwiatkowski et al, 2004, 2006; Zhang et al, 2005; Feng et al, 2008; Shimomura et al, 2010; Du et al, 2011; Umegaki et al, 2011). The majority of KRT9 mutations are located in the first exon, which encodes a highly conserved coiled segment of the α‐helical rod domain; these mutations generally affect the formation of intermediate filaments and keratin heterodimerization (Reis et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…4). All the patients suffered from diffuse palmar and plantar hyperkeratosis [9, 10, 42, 45, 54, 55]. Camptodactyly [9], hyperhidrosis [9, 55], and knuckle pads [9, 10, 55], were observed in one, two, and three families, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Among the seven KRT9 gene mutations identified in the 2B rod domain (including our mutation) [9, 10, 42, 45, 54, 55], five of them are closely distributed, ranging from p.Tyr454 to p.Leu458 [9, 42, 45, 54] (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…in 2008 . At the same codon, two mutations (c.470T>A and c.470T>C), which transformed methionine into lysine and threonine, respectively, has also been reported . Studies have shown that the initiative gene sequence of the coiled 1A region was confirmed by the first 15 highly conserved amino acids of 1A.…”
Section: Twenty‐six Pathogenic Mutations Of Krt9 Associated With Epidmentioning
confidence: 99%